Dynamical classical superfluid-insulator transition in a Bose-Einstein condensate on an optical lattice - Adhikari, S. K. (Iop Publishing Ltd, 2003)
We predict a dynamical: classical superfluid-insulator transition in a Bose-Einstein condensate (BEC) trapped in combined optical and axially symmetrical harmonic potentials initiated by the periodic modulation of the radial trapping potential. The transition is marked by a loss of phase coherence in the BEC and a subsequent destruction of the interference pattern upon free:expansion. For a weak modulation of the radial potential the phase coherence is maintained. For a stronger modulation and a longer holding time in the modulated trap, the phase coherence is destroyed thus signalling a classical superfluid-insulator transition. The results are illustrated by a complete numerical solution of the axially symmetrical mean-field Gross-Pitaevskii equation for a repulsive BEC. Suggestions for future experimentation are-made.